Digital Workflow for Edentulous Patients with Implant-Supported Fixed Prostheses: A Fully Digital Technique - Seung Wook Jung; Yi-Qin Fan; Chunui Lee (Dentistry Journal, 2022)
Dentists have made prostheses using traditional methods, which are inconvenient and time-consuming. It includes functional impression taking, plaster model production, wax rim production, intermaxillary relationship and occlusal plane setting, artificial tooth arrangement, denture polymerization, polishing, etc. To make prostheses in this way, the patient has to visit the dentist several times, and it takes a long time for them to receive treatment. In addition, the potential for errors associated with the denture-manufacturing process and the use of denture materials has always existed. However, the recent use of digital technology in dentistry has made it possible to create digital prostheses. Several techniques for the immediate loading of implants with a fixed prostheses in edentulous patients have been developed. However, these techniques are partially digital techniques that include laboratory work for prosthesis fabrication. This article aimed to describe a fully digital technique for implant-supported fixed prostheses. It includes intra-oral scanning of edentulous patients, implant placement planning, and final prosthesis fabrication. This technique facilitates a simple and more efficient immediate restoration after implant placement without using stone casts.